2015
DOI: 10.4149/av_2015_01_3
|View full text |Cite
|
Sign up to set email alerts
|

Next generation sequencing technologies: Tool to study avian virus diversity

Abstract: Summary. -Increased globalisation, climatic changes and wildlife-livestock interface led to emergence of novel viral pathogens or zoonoses that have become serious concern to avian, animal and human health. High biodiversity and bird migration facilitate spread of the pathogen and provide reservoirs for emerging infectious diseases. Current classical diagnostic methods designed to be virus-specific or aim to be limited to group of viral agents, hinder identifying of novel viruses or viral variants. Recently de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 93 publications
0
7
0
1
Order By: Relevance
“…Thus, the full genomic characterisation of emerging ARV field strains will provide more detailed molecular data to better understand ARV mutations and/or recombination events that may influence the epidemiology and pathogenicity of the virus. We are currently sequencing the full genome of the MS01 strain using the MiSeq next-generation sequencing system (Illumina, San Diego, CA, USA) 32 33 34 . The full genome sequence will allow us to determine the locations of mutated sites in the complete sequences of all 10 genome segments by comparison with reference strain S1133.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the full genomic characterisation of emerging ARV field strains will provide more detailed molecular data to better understand ARV mutations and/or recombination events that may influence the epidemiology and pathogenicity of the virus. We are currently sequencing the full genome of the MS01 strain using the MiSeq next-generation sequencing system (Illumina, San Diego, CA, USA) 32 33 34 . The full genome sequence will allow us to determine the locations of mutated sites in the complete sequences of all 10 genome segments by comparison with reference strain S1133.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence-independent techniques, such as next generation sequencing, have allowed the detection of avian viral genome diversity from healthy and affected birds Kapgate et al, 2015). The comparative metagenomics studies revealed ChPV genomic sequence diversity identified from RSSaffected and unaffected broilers (Devaney et al, 2016;Lima et al, 2017), and divergent turkey parvovirus sequences from turkey faeces (Reuter et al, 2014).…”
Section: Diagnosismentioning
confidence: 99%
“…Identification methods based on culture have disadvantages, such as long turnaround time, increased biohazard risks, and culture bias. The high-throughput feature of NGS enables the recovery of pathogen genomes from noncultured samples, and offers the potential for highly accurate pathogen identification and rapid clinical diagnoses [ 4 12 ]. Many researchers have reported the NGS-based identification of pathogens from various noncultured samples [ 13 21 ], such as Old World arenavirus (brain et al) [ 17 ], influenza virus (nasopharyngeal aspirate) [ 18 ], norovirus (feces) [ 18 ], dengue virus [ 19 ], yellow fever virus (serum) [ 20 ], Shiga-toxigenic Escherichia coli O104:H4 (feces) [ 21 ], and most recently, Ebola virus (serum et al) [ 13 16 ].…”
Section: Resultsmentioning
confidence: 99%